The balance between memory and regulatory cell populations in kidney transplant recipients with operational tolerance - Süsal, Caner; Alvarez, Cristiam M; Benning, Louise; Daniel, Volker; Zeier, Martin; Schaier, Matthias; Morath, Christian; Speer, Claudius (Clinical & experimental immunology, 2024)
Donor-reactive memory cells represent a barrier to long-term kidney graft survival. A better understanding of regulatory mechanisms that counterbalance alloreactive memory responses may help to identify patients with operational tolerance. This prospective study investigated the equilibrium between memory T-cell subsets and regulatory T or B cells (Tregs, Bregs) in peripheral blood of kidney transplant recipients with operational tolerance (N = 8), chronic rejection (N = 8), and different immunosuppressive treatment regimens (N = 81). Patients on hemodialysis and healthy individuals served as controls (N = 50). In addition, the expression of Treg- and Breg-associated molecule genes was analyzed. Patients with chronic rejection showed a disrupted memory T-cell composition with a significantly higher frequency of circulating CD8+ terminally differentiated effector memory (TEMRA) T cells than patients with operational tolerance, patients on hemodialysis, or healthy controls (P < 0.001). Low frequency of CD8+ TEMRA and high frequency of Tregs and transitional Bregs were found in operationally tolerant patients. Consequently, operationally tolerant patients showed, as compared to all other transplant recipients with different immunosuppressive regiments, the lowest ratios between CD8+ TEMRA T cells and Tregs or Bregs (for both P < 0.001). Moreover, a specific peripheral blood transcription pattern was found in operationally tolerant patients with an increased expression of Breg- and Treg-associated genes CD22 and FoxP3 and a decreased FcγRIIA/FcγRIIB transcript ratio (for all P < 0.001). In conclusion, monitoring the balance between circulating CD8+ TEMRA T cells and regulatory cell subsets and their transcripts may help to distinguish transplant recipients with operational tolerance from recipients at risk of graft loss.
Veröffentlicht: 23. Februar 2024
Gesehen am 16.08.2024